Slight respiratory irritation but not inflammation in mice exposed to (1→3)-β-D-glucan aerosols - A. Korpi; J.-p. Kasanen; V.-m. Kosma; R. Rylander; A.-l. Pasanen (Hindawi Limited, 2003)
Airway irritation effects after single and repeated inhalation exposures to aerosols of β-glucan (grifolan) were investigated in mice. In addition, the effects on serum total immunoglobulin E (IgE) production and histopathological inflammation in the respiratory tract were studied. The β-glucan aerosols provoked slight sensory irritation in the airways, but the response was not concentration dependent at the levels studied. Slight pulmonary irritation was observed after repeated exposures. No effect was found on the serum total IgE levels, and no signs of inflammation were seen in the airways 6 h after the final exposure. The results suggest that, irrespective of previous fungal sensitization of the animals, inhaled β-glucan may cause symptoms of respiratory tract irritation but without apparent inflammation. Respiratory tract irritation reported after inhalation of fungi may not be entirely attributed to β-glucan.